Multi-domain modelling and simulation of an automated manual transmission system based on Modelica. (2015) - Huang, Hua; Nowoisky, Sebastian; Knoblich, René; Gühmann, Clemens
With the continuous growth in the emission requirements and higher riding comfort demand, the shift quality takes more and more an important role in automated transmission control algorithms. In order to effectively optimise the corresponding control parameters and functions in the transmission control units (TCU), the model-based calibration is a suitable method. For this purpose, a detailed dynamic model, which provides a virtual platform for the shift quality optimisation, is imperative and necessary. In this paper, a five-speed automated manual transmission (AMT) is used as a research object and a detailed Modelica®-based hydro-mechanical dynamic model is presented. Model simulations are also compared with the measurements from a test bench. Testing results show the dynamic model can effectively describe detailed gear shifting phenomena.